Perceptions on Information and Communication Technology among the Faculty of a Mexican University: the South University Center of the University of Guadalajara - María Cristina López De la Madrid; Adolfo Espinoza de los Monteros Cárdenas; Katiuzka Flores Guerrero (Universidad Autónoma de Baja California, 2006)
It is the faculty members who can generate the greatest changes in universities around the world, based on the establishment of defined policies. On the teachers falls the responsibility of training and orienting students-the primary users of these institutions. The objective of the present study is to define what have been the perceptions and the changes among teaching faculty in the process of implementing information technologies in the South University Center, University of Guadalajara (Mexico). Questionnaires were distributed to 42 of the institution's 320 teachers. Four areas were addressed: technological infrastructure; teacher training and support; reasons for implementing information and communication technologies; and modification of the teaching/learning process. Based on the surveyees' answers, categories of analysis were developed; these were used to define the needs of the group. Next a process of research-action was carried out with a group of faculty interested in changing their educational practices; the group members received several different training courses. Most of the professors accepted the implementation of the technologies in their academic programs, although many of them had not put them into practice. On the other hand, they pointed out the importance of having the necessary infrastructure and training support, as well as constant technical, methodological and didactic assistance.